Prevention of Neural Tube Defects in Europe: A Public Health Failure - Morris, Joan K.; Addor, Marie-Claude; Ballardini, Elisa; Barisic, Ingeborg; Barrachina-Bonet, Laia; Braz, Paula; Cavero-Carbonell, Clara; Den Hond, Elly; Garne, Ester; Gatt, Miriam; Haeusler, Martin; Khoshnood, Babak; et al. (Frontiers in Pediatrics, 2021)
Objective Thirty years ago it was demonstrated that folic acid taken before pregnancy and in early pregnancy reduced the risk of a neural tube defect (NTD). Despite Public Health Initiatives across Europe recommending that women take 0.4mg folic 290 acid before becoming pregnant and during the first trimester, the prevalence of NTD pregnancies has not materially decreased in the EU since 1998, in contrast to the dramatic fall observed in the USA. This study aimed to estimate the number of NTD pregnancies that would have been prevented if flour had been fortified with folic acid in Europe from 1998 as it had been in the USA. Design and Setting Estimates of NTD prevalence from 1998 to 2017 were used to predict the number of NTD pregnancies that would have been prevented if folic acid fortification had been implemented in the 28 countries who were members of the European Union in 2019 using data from 35 EUROCAT congenital anomaly registries and literature searches for population serum folate levels and for folic acid supplementation. Results From 1998 to 2017 an estimated 95,213 NTD pregnancies occurred amongst 10.4 million births in the 28 countries in the EU, a prevalence of 0.92 per 1000 births. The median serum folate level in Europe over this time period was estimated to be 13.3 µg/L. There is a lack of information about women taking folic acid supplements before becoming pregnant and during the first trimester of pregnancy, with one meta-analysis indicating that around 25% of women did so. An estimated 15,400 pregnancies may have been prevented if the European countries had implemented fortification at the level adopted by the USA in 1998 and 25% of women took folic acid supplements. An estimated 20,500 would have been prevented if no women too folic acid supplements. Conclusions This study suggests that failure to implement mandatory folic acid fortification in the 28 European countries has caused, and continues to cause, neural tube defects to occur in almost 1000 pregnancies every year.